Preservation of Indonesian language Buttonscarves and Erigo in public spaces (Implementation of Law Number 24 of 2009 and PERMENDAG No. 73/M-Dag/Per/9/2015) - Juwita, Silvia Ratna; Anshori, Dadang S; Sunendar , Dadang; Kuwing, Asiyah (Universitas Ahmad Dahlan, 2023)
The study in this article describes the application of regulations on the use of the Indonesian language on trademarks already contained in Law Number 24 of 2009 which is supported by PERMENDAG No. 73/M-Dag/Per/9/2015 on local fashion products that enter the international market. The aim is to map the application of the use of the Indonesian language that has been carried out by local fashion products that are worldwide because it can help efforts to develop Indonesian into an international language. This study uses a qualitative approach with descriptive analytical specifications and aims to provide a comprehensive, detailed and systematic description. The data is taken from the official website pages of two local fashion product brands that are worldwide, Buttonscarves and Erigo. It was found that Buttonscarves did not fulfill the application of the use of the Indonesian language regarding the trademark name due to the use of the English word to make the Buttonscarves brand more easily accepted in the international market, while for Erigo it cannot be said that it is fulfilled/not because it is not part of the Indonesian word contained in in the Kamus Besar Bahasa Indonesia (KBBI).